Respuesta :
f(x)= -2 (x - 2) ( x - 4)
if x=2 ⇒ f(x)=y=0 ⇒ graph of f(x) intercept x axis in (2,0)
if x=4 ⇒ f(x)=y=0 ⇒ graph of f(x) intercept x axis in (4,0)
if x=0 ⇒f(x)= -2 *(-2)*(-4)= - 16 ⇒ graph of f(x) intercept y axis in (0,- 16)
⇒ f(x)= -2 (x - 2) ( x - 4) is the answer
if x=2 ⇒ f(x)=y=0 ⇒ graph of f(x) intercept x axis in (2,0)
if x=4 ⇒ f(x)=y=0 ⇒ graph of f(x) intercept x axis in (4,0)
if x=0 ⇒f(x)= -2 *(-2)*(-4)= - 16 ⇒ graph of f(x) intercept y axis in (0,- 16)
⇒ f(x)= -2 (x - 2) ( x - 4) is the answer
Answer: The correct option is (C) [tex]f(x)=-2(x-2)(x-4).[/tex]
Step-by-step explanation: We are given to select the correct equation such that its graph has x-intercepts at (2, 0) and (4, 0) and a y-intercept of (0, –16).
We know that the co-ordinates of the x-intercepts and the y-intercept will satisfy the equation.
So, we will check the given functions one by one.
Option (A) is
[tex]f(x)=-(x-2)(x-4).[/tex]
Here,
[tex]f(2)=-(2-2)(2-4)=0,\\\\f(4)=-(4-2)(4-4)=0,\\\\f(0)=-(0-2)(0-4)=-8\neq -16.[/tex]
So, this option is not correct.
Option (B) is
[tex]f(x)=-(x+2)(x+4).[/tex]
Here,
[tex]f(2)=-(2+2)(2+4)=-24\neq 0.[/tex]
So, this option is not correct.
Option (C) is
[tex]f(x)=-2(x-2)(x-4).[/tex]
Here,
[tex]f(2)=-2(2-2)(2-4)=0,\\\\f(4)=-2(4-2)(4-4)=0,\\\\f(0)=-2(0-2)(0-4)=-16.[/tex]
So, this option is correct.
Option (D) is
[tex]f(x)=-2(x+2)(x+4).[/tex]
Here,
[tex]f(2)=-2(2+2)(2+4)=-48\neq 0.[/tex]
So, this option is not correct.
Thus, The correct equation is [tex]f(x)=-2(x-2)(x-4).[/tex]
Option (C) is correct.